Suppression of muscle wasting by the plant‐derived compound ursolic acid in a model of chronic kidney disease. Issue 2 (17th November 2016) - Yu, Rizhen; Chen, Ji‐an; Xu, Jing; Cao, Jin; Wang, Yanlin; Thomas, Sandhya S.; Hu, Zhaoyong
Abstract: Background: Muscle wasting in chronic kidney disease (CKD) and other catabolic disorders contributes to morbidity and mortality, and there are no therapeutic interventions that regularly and safely block losses of muscle mass. We have obtained evidence that impaired IGF‐1/insulin signalling and increases in glucocorticoids, myostatin and/or inflammatory cytokines that contribute to the development of muscle wasting in catabolic disorders by activating protein degradation. Methods: Using in vitro and in vivo models of muscle wasting associated with CKD or dexamethasone administration, we measured protein synthesis and degradation and examined mechanisms by which ursolic acid, derived from plants, could block the loss of muscle mass stimulated by CKD or excessive levels of dexamethasone. Results: Using cultured C2C12 myotubes to study muscle wasting, we found that exposure to glucocorticoids cause loss of cell proteins plus an increase in myostatin; both responses are significantly suppressed by ursolic acid. Results from promoter and ChIP assays demonstrated a mechanism involving ursolic acid blockade of myostatin promoter activity that is related to CEBP/δ expression. In mouse models of CKD‐induced or dexamethasone‐induced muscle wasting, we found that ursolic acid blocked the loss of muscle mass by stimulating protein synthesis and decreasing protein degradation. These beneficial responses included decreased expression of myostatin and inflammatory cytokines (e.g. TGF‐β, IL‐6 and TNFα), which are initiators of muscle‐specific ubiquitin‐E3 ligases (e.g. Atrogin‐1, MuRF‐1 and MUSA1). Conclusions: Ursolic acid improves CKD‐induced muscle mass by suppressing the expression of myostatin and inflammatory cytokines via increasing protein synthesis and reducing proteolysis.